The Model of Islamic Boarding School Economic Development In Hidayatullah Islamic Boarding School Mataram City and Darussalam West Lombok - Mawardi Saleh; Lalu Agus Satriawan (Program Studi Ekonomi Islam Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Syarifuddin Lumajang, 2020)
In its historical setting pondok pesantren (islamic boarding school) present in the form of traditional educational institutions whose activities are more focused on the study of religious books and the organization of religious education. But since the 1970s Islamic boarding school began to evolve and organize public education, involved in social activities even in the economic field. Witnessing this phenomenon, it was felt necessary to conduct a study of the Islamic boarding school economic development model in pondok pesantren Hidayatullah, Mataram City and pondok pesantren Darussalam in West Lombok. The focus of the study is twofold: the potentials of the pondok pesantren and the Islamic boarding school economic development model. The results of the study are: (1) The economic potentials owned by Hidayatullah and Darussalam boarding schools are the leadership, students, teachers and education activities, (2) The economic development model carried out by Hidayatullah and Darussalam is an integrated model realized in the form of a top down model and bottom up the model that both models work by combining the strength of the leadership element with the strength of the element of asatidz and santri